ON IMAGINATION AND UNDERSTANDING. GADAMER AND CRITICISM OF KANT’S AESTHETIC IMAGINATION - LENGYEL, Zsuzsanna Mariann (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
In this paper, I would like to investigate how Gadamer explores the hermeneutic potential of Kant’s aesthetic theory in the third Critique with regard to the notion of imagination. For the first time, by making some references, Gadamer discussed the question of imagination in his Truth and Method of 1960, and we can read as a further substantial contribution his essay entitled Anschauung und Anschaulichkeit (Intuition and Intuitiveness) published in 1980. Although Gadamer’s approach was influenced by some Heideggerian impulses, he offered another alternative that is completely different from Heidegger’s one. I shall argue that even if the question of imagination is not so much stressed by Gadamer, it proves important to the development and ontological basis of the Gadamerian hermeneutics in Wahrheit und Methode. My hypothesis is that through the themes of intuition and education (Bildung), the imagination is concerned with the human understanding and our interpreting work, thus, its significance transcends the scope of aesthetics.